Sustained in vivo signaling by long-lived IL-2 induces prolonged increases of regulatory T cells. (January 2015) - Bell, Charles J.M.; Sun, Yongliang; Nowak, Urszula M.; Clark, Jan; Howlett, Sarah; Pekalski, Marcin L.; Yang, Xin; Ast, Oliver; Waldhauer, Inja; Freimoser-Grundschober, Anne; Moessner, Ekkehard; Umana, Pablo; et al.
Abstract: Regulatory T cells (Tregs) expressing FOXP3 are essential for the maintenance of self-tolerance and are deficient in many common autoimmune diseases. Immune tolerance is maintained in part by IL-2 and deficiencies in the IL-2 pathway cause reduced Treg function and an increased risk of autoimmunity. Recent studies expanding Tregs in vivo with low-dose IL-2 achieved major clinical successes highlighting the potential to optimize this pleiotropic cytokine for inflammatory and autoimmune disease indications. Here we compare the clinically approved IL-2 molecule, Proleukin, with two engineered IL-2 molecules with long half-lives owing to their fusion in monovalent and bivalent stoichiometry to a non-FcRγ binding human IgG1. Using nonhuman primates, we demonstrate that single ultra-low doses of IL-2 fusion proteins induce a prolonged state of in vivo activation that increases Tregs for an extended period of time similar to multiple-dose Proleukin. One of the common pleiotropic effects of high dose IL-2 treatment, eosinophilia, is eliminated at doses of the IL-2 fusion proteins that greatly expand Tregs. The long half-lives of the IL-2 fusion proteins facilitated a detailed characterization of an IL-2 dose response driving Treg expansion that correlates with increasingly sustained, suprathreshold pSTAT5a induction and subsequent sustained increases in the expression of CD25, FOXP3 and Ki-67 with retention of Treg-specific epigenetic signatures at FOXP3 and CTLA4 . Highlights: Fusion of IL-2 to human IgG1 extends IL-2 half-life and efficiency of Treg induction. Long-lived IL-2 efficacy allows for lower doses thereby increasing Treg specificity. Sustained pSTAT5a induction in Tregs by long-lived IL-2 correlates with Treg expansion. Increased stoichiometry, IgG-(IL-2)2, increases affinity and in vivo effects on Tregs